Graphic Feedback, Performance Feedback, and Goal Setting Increased Staff Compliance With a Data Collection Task at a Large Residential Facility. Issue 1 (2nd January 2016) - Gil, Pamela J.; Carter, Stacy L.
ABSTRACT: Because of budgetary constraints, human service organizations frequently expect consultants to recommend methods to enhance staff performance that require little or no additional funding. The current study utilized a multiple baseline across settings design to evaluate and compare the effects of a single intervention and a packaged intervention including graphic feedback and goal setting on approximately 200 direct care staff as a group, to improve the data collection procedure at a residential treatment facility. The single intervention showed some improvement, whereas the packaged intervention yielded substantial improvements and was maintained.